A new modified scaled conjugate gradient method for large-scale unconstrained optimization with non-convex objective function. (4th July 2019) - Khoshgam, Zahra; Ashrafi, Ali
Abstract : In this paper, according to the fifth-order Taylor expansion of the objective function and the modified secant equation suggested by Li and Fukushima, a new modified secant equation is presented. Also, a new modification of the scaled memoryless BFGS preconditioned conjugate gradient algorithm is suggested which is the idea to compute the scaling parameter based on a two-point approximation of our new modified secant equation. A remarkable feature of the proposed method is that it possesses a globally convergent even without convexity assumption on the objective function. Numerical results show that the proposed new modification of scaled conjugate gradient is efficient.